Structure of «Songs of Home» of The Black Heralds - Lozano Alvarado, Saniel (2019)
«Songs of Home», the shortest section of The Black Heralds, is composed of five poems, four of which are developed in the context of the home, in an intimate and family environment, with a marked subjective, emotional and spiritual character, almost always dominated by the image of the father. The linear dimension of the time combines the present with the past, with a strong psychological character. The integration of the three magnitudes —present, past and future— only occurs in the poem «Enereida». The perspective of construction of the poems is personal, as something primordial that happens, feels and worries the enunciator himself; therefore, other people do not feel or consider themselves represented. The title is connotative and bisemic, because strictly it does not allude to any song or melody, but to the intimate and homelike atmosphere. The possible meanings highlight the value of the home, the love of the father, the absence of the brother, the feeling of emptiness and loneliness. The language starts from a popular substrate, but endowed with an admirable artistic wealth.